Development of a position detection technique for UWB chipless RFID tagged object - Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Alam, A. H. M. Zahirul (2013)
Ultra wideband (UWB) chipless RFID tag of microwave band is used to study the location of an object. Two microwave antennas for narrow bandwidth beam used for scanning purpose. The antennas are mounted on two digital stepper motor driven systems. The location of the tagged object is measured from the angular position of the antennas. A squire space of 25 m2 and 1 m2 resolution are used for the project. The simulation result showed that the location detection is almost error free. The accuracy of the position detection has a limitation and it depends on the resolution of the system. The system may be used in the warehouse/store for auto inventory and location finding purpose.